Pengaruh Pelatihan dan Insentif terhadap Kinerja Perawat di RSUD Pambalan Batung Amunta Kalimatan Selatan - Afthina, Rifka Ellya; Hidayat, Muhammad Syamsu (Universitas Ahmad Dahlan, 2022)
To train employees with knowledge, skills and abilities that suit the needs of the company, training is required. Incentives are a form of remuneration that can improve work performance. This study aims to determine whether or not there is an influence between training and incentives on the performance of nurses at Pambalah Batung Amuntai Regional General Hospital in South Kalimantan. The type of research used is quantitative research. Sampling techniques used in this study is to use probability sampling technique that is proportionate stratified random sampling by using slovin formula. The research population is all part of the health workers, especially nurses in the inpatient section of Pambalah Batung Amuntai Regional General Hospital numbered 143 and to be sampled in this study was 117 people. The variables of training and incentives affect the performance of nurses of Pambalah Batung Amuntai Hospital in South Kalimantan. The coefesien value of determination is 0.194 which means that all free variables are training and incentives that affect performance by 19.4%, the remaining 80.6% which is influenced by other factors that are not studied. The variables of training and incentives have a significant influence on the performance of nurses at Pambalah Batung Amuntai Hospital in South Kalimantan.